Upaya Peningkatan Strategi Pemasaran Produk UMKM Es Cendol Melalui Pemasaran Digital - Oktavia Pramasta Sari; Jojok Dwiridotjahtjono (Universitas Muhammadiyah Manado, 2023)
Real Work Lecture (KKN) is a form of service carried out by students by being directly involved in the community and in these activities students are faced with various problems that exist in society so that students must be able to solve these problems. In this KKN activity it was carried out in Blitar City to be precise in the Kauman Village. One of the MSMEs in Kauman Village named Es Cendol